Birds as Biodiversity Barometers in the Anthropocene: Updating Concepts, Correcting Biases, and Scaling Indicators for Policy Impact - Daud Yusuf; Dewi Wahyuni K Baderan; Sukirman Rahim; Zuliyanto Zakaria (Postgraduate, University of Mataram, 2026)
Birds are powerful biodiversity indicators due to their wide distribution and responsiveness to environmental pressures. Building on prior reviews, we synthesize methodological advances to update the Multi-species Bird Index (MSI) field. This study recaps limitations like European/breeding-season biases and uncertainty gaps while integrating recent studies that expand analytical rigor. Advances in passive acoustic monitoring, remote sensing, and trait-based models now improve species selection and reduce detectability errors. We translate these into practical guidance for policy application and a research agenda emphasizing seasonal completeness. The synthesis underscores birds’ role as decision ready barometers and provides a blueprint for robust monitoring. Birds serve as premier biodiversity barometers due to their cosmopolitan distribution and sensitivity to anthropogenic pressures. However, traditional Multi species Bird Indicators (MSIs) often suffer from significant Europe-centric and breeding-season biases that limit their global policy impact. This study synthesizes recent methodological breakthroughs to update the MSI framework. We evaluate the integration of Passive Acoustic Monitoring (PAM), high-resolution remote sensing (ALS LiDAR), and trait-based selection criteria into standard monitoring protocols. Our synthesis reveals that combining automated sensor networks with hierarchical Bayesian models effectively mitigates detectability errors and fills critical data gaps in under-represented regions. Furthermore, linking avian indicators with carbon sequestration and equity metrics allows for more robust prioritization of Nature based Solutions (NbS). We provide a practical blueprint for next-generation indicators that emphasize seasonal completeness and statistical rigor. By shifting from retrospective reports to forward-looking policy tools, these refined barometers can more accurately track progress toward global biodiversity targets.